Migracije v času pandemije covid-19 - Zavratnik, Simona (Teorija in praksa, 2021)
The text studies the connection between the Covid-19 pandemic, migration and exclusion from a safe living space. The main argument addresses the complexity of the new circumstances of migration and refugee routes, when borders became impermeable to all, not only refugees. In addition, the issue of international mobility is joined by the threatening contagious Other. The corona crisis has paradoxically seen sedentariness become the new imperative of global mobility. Our thesis is that the limits of the pandemic have become the limits of mobility, where the stayathome imperative as the main element of the anti-corona policies overlooks social groups and many individuals on the social margins who have no access to a safe isolated space, including migrants and refugees.
Keywords: COVID-19; družbena neenakost; migracije; migrations; mobility; mobilnost; pandemics; pandemije; social inequality